2018
DOI: 10.1096/fj.201800109r
|View full text |Cite
|
Sign up to set email alerts
|

The Mfge8‐α8β1;1‐PTEN pathway regulates airway smooth muscle contraction in allergic inflammation

Abstract: Asthma affects ∼300 million people worldwide. Despite multiple treatment options, asthma treatment remains unsatisfactory in a subset of patients. Airway obstruction is a hallmark of allergic asthma and is largely due to airway smooth muscle hypercontractility induced by airway inflammation. Identification of molecular pathways that regulate airway smooth muscle hypercontractility is of considerable therapeutic interest. We previously identified roles for milk fat globule epidermal growth factor-like 8 (Mfge8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Our findings illuminated previously unknown characteristics of α8β1: de novo expression in activated HSCs in vitro and in vivo , upregulation of αSMA, and TGFβ activation on HSCs and fibroblasts. These findings fit well with previous observations of Itga8 expression in other contractile cells, including airway [15] and gastric [16] smooth muscle cells, arrector pili [17] and sensory hair cells [18]. Recent single‐cell RNA‐sequencing data from NASH mice revealed exclusive Itga8 expression in HSCs in liver cells [19].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings illuminated previously unknown characteristics of α8β1: de novo expression in activated HSCs in vitro and in vivo , upregulation of αSMA, and TGFβ activation on HSCs and fibroblasts. These findings fit well with previous observations of Itga8 expression in other contractile cells, including airway [15] and gastric [16] smooth muscle cells, arrector pili [17] and sensory hair cells [18]. Recent single‐cell RNA‐sequencing data from NASH mice revealed exclusive Itga8 expression in HSCs in liver cells [19].…”
Section: Discussionsupporting
confidence: 90%
“…MAST4 is a part of the PTEN signaling pathway (Valiente et al, 2005;Sotelo et al, 2012), which has been confirmed to mediate the IL-13-induced stimulation, hyper-responsiveness, and inflammation, of airway smooth muscles, thus validating this predicted target gene (Jiang et al, 2012). Similar conclusions have also been further validated in later studies (Hu et al, 2014;Khalifeh-Soltani et al, 2018). Therefore, MAST4 is definitely correlated with the interleukinmediated stimulation of airway smooth muscles.…”
Section: Signatures On the Epigenetics Levelsupporting
confidence: 53%
“…Notably, our mechanistic studies suggest that these effects did not occur through modulation of actin-myosin cross-bridge interactions, but rather by modulating cellular tethering to the extracellular matrix. Members of the integrin family have previously been described to have effects on airway hyperresponsiveness (21,22) by modulating intracellular pathways resulting in downstream regulation of myosin light chain phosphorylation, including interaction with SSAT and PTEN. However, there is a growing body of evidence supporting the role of independently regulated cellular processes, including cytoskeletal stabilization (23,24), matrix stiffness (25,26), and intercellular tethering (27,28), in modulating force transmission throughout smooth muscle bundles.…”
Section: Discussionmentioning
confidence: 99%